2008
DOI: 10.1128/jcm.01615-07
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination of Herpes Simplex Virus Type 2 Strains by Nucleotide Sequence Variations

Abstract: We determined the polymorphous 400-bp regions in UL53, US1, and US4 for the discrimination of herpes simplex virus type 2 (HSV-2) strains. Thirty-six HSV-2 clinical strains could be differentiated into 35 groups using these three regions and into 36 groups by additional analysis of three noncoding regions previously reported as polymorphous.Herpes simplex virus type 2 (HSV-2) often causes genital herpes and, occasionally, meningitis, neonatal infections, and acute retinal necrosis. The study of the relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 13 publications
2
9
0
Order By: Relevance
“…While TK, POL, and gD genes were found highly conserved among HSV-2 isolates, gB and gG genes offered a noticeable number of variability hot spots which made these genes suitable tools for the differentiation of viral strains. This conclusion is supported by the previous use of the variability of these genes for classification of HSV-2 isolates [Terhune et al, 1998;Norberg et al, 2007;Kaneko, 2008;Schmidt-Chanasit et al, 2010;]. Moreover, many of the genetic polymorphisms of gB and gD described in the present study have been already reported in previous publications [Terhune et al, 1998;Norberg et al, 2007;Kaneko, 2008].…”
Section: Discussionsupporting
confidence: 91%
“…While TK, POL, and gD genes were found highly conserved among HSV-2 isolates, gB and gG genes offered a noticeable number of variability hot spots which made these genes suitable tools for the differentiation of viral strains. This conclusion is supported by the previous use of the variability of these genes for classification of HSV-2 isolates [Terhune et al, 1998;Norberg et al, 2007;Kaneko, 2008;Schmidt-Chanasit et al, 2010;]. Moreover, many of the genetic polymorphisms of gB and gD described in the present study have been already reported in previous publications [Terhune et al, 1998;Norberg et al, 2007;Kaneko, 2008].…”
Section: Discussionsupporting
confidence: 91%
“…This variation is higher than the maximal 0.4% variance noted by Norberg et al among 47 strains sequenced in the US4, US7, and US8 regions. Kaneko et al noted that many HSV-2 genes were completely invariant in Japan (e.g., UL4, UL5, UL12, and 9 other genes) (15). The low dN/dS ratio observed for UL23 is consistent with active selection to preserve certain amino acid sequences despite the apparent tolerance for amino acid changes in many locations.…”
Section: Discussionmentioning
confidence: 70%
“…In our data set, sequences from Peru were admixed with African sequences in all major branches of the UL23 neighbor-joining tree. Kaneko et al sequenced 36 HSV-2 genes from 36 subjects in Japan (15). They analyzed UL3, US1, and US4, their most divergent loci, as trees and noted that they had differing topologies.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, LAMP is more stable than PCR and qPCR (Francois et al, 2011). As the presence of exogenous DNA and inhibitors in clinical samples has less impact on the sensitivity of LAMP than PCR, DNA purification from samples for LAMP detection may be omitted (de Franchis et al, 1988, Kaneko et al, 2007. A cold chain is essential when preparing the master mix for PCR, while it is not mandatary in the case of LAMP.…”
Section: Discussionmentioning
confidence: 99%
“…Loop-mediated isothermal amplification (LAMP) assays rely on auto-cycling strand displacement DNA synthesis in the presence of Bst DNA polymerase under isothermal conditions within 60 min (Notomi et al, 2000;Ushikubo, 2004). In contrast to Taq DNA polymerase used in PCR, the Bst DNA polymerase is resistant to inhibitors present in crude biological samples (Kaneko et al, 2007). As four or six specific primers that recognize six or eight distinct sequences on the target DNA are required, LAMP has been shown to amplify target DNA with high specificity and is widely used in the clinical diagnosis of epidemic bacteria Knight et al, 2014), viruses (Poon et al, 2004;Curtis et al, 2014), parasites (Li et al, 2012;Ni et al, 2014) and fetal sex identification (Fu et al, 2011), as well as detection of the hypervirulent strain and toxin types of C. difficile (Kato et al, 2005;Norén et al, 2011;Boyanton et al, 2012).…”
Section: Introductionmentioning
confidence: 99%